Seismic imaging of an active fluid conduit below Scanner Pockmark, Central North Sea. (November 2021) - Schramm, Bettina; Berndt, Christian; Dannowski, Anke; Böttner, Christoph; Karstens, Jens; Elger, Judith
Abstract: Subsurface CO2 storage is a key strategy to reduce greenhouse gas emission, but leakage of CO2 along natural fluid pathways may affect storage formation integrity. However, the internal structure and the physical properties of these focused fluid conduits are poorly understood. Here, we present a three-dimensional seismic velocity model of an active fluid conduit beneath the Scanner Pockmark in the Central North Sea, derived from ocean-bottom seismometer data. We show that the conduit, which manifests as a pipe structure in seismic data, is separated into two parts. The upper part, extending to 260 m depth, i.e. 110 m below the seafloor, is characterised by seismic velocities up to 100 m/s slower than the surrounding strata. The deeper part is characterized by a 50 m/s seismic velocity increase compared to background velocity. We suggest that the upper part of the pipe structure represents a network of open fractures, partly filled with free gas, while the reason for the velocity increase in the lower part remains speculative. These observations suggest that active pipes can be internally heterogeneous with some intervals probably being open fluid pathways and other intervals being closed. This study highlights the complexity in evaluating focused fluid conduits and the necessity of their detailed assessment when selecting CO2 storage sites. Highlights: Unprecedented dense coverage of ocean-bottom seismometer data reveals seismic velocity variations within a vertical fluid pathway. There are zones of both positive (faster) and negative (slower) velocity within the fluid pathway compared to the background formation velocities. Velocity reductions are related to free gas in the fluid pathway, while the reason for velocity increases is unclear but potentially caused by cementation.